Prediction of Financial Distress in Indian Firms Using Altman Z- Score Model - SHARMA, MONIKA; PATRA, DR. GOVIND (The journal of contemporary issues in business and government, 2021)
Recently, it is notable that business environment is everchanging. Due to dynamic business environment, companies have to face many problems without coping up with the changed environment, companies are not able to survive in the market. If the company is slow in responding to changes in the environment any social economic and technological changes may affects its performance. India is a developing country. Central and state governments take many industrial reform initiatives for the industrial growth. But due to enhance uncertainty scenario, many companies have been suffering from distress and bankruptcy has become very major problem in India because it’s become challenging for the companies to survive in the market in ever growing business environment. Companies can escape from the situation of the bankruptcy by the constantly update themselves.